The avifauna of Lo Go - Xa Mat National Park, Tay Ninh Province - Hung, Le Minh; Tordoff, A. W. (Academia Journal of Biology, 2015)
The total of 177 bird species belonging to 16 orders, 49 families were recorded in the Logo - Xamat National Park, Tayninh province. Of the 177 species, 4 species are listed in the 2000 IUCN Red List of Threatened Species (IUCN 2000) as globally threatened or near-threatened, and 8 species are listed in the Red Data Book of Vietnam (Anon. 1992). Furthermore, the Logo - Xamat supports two (germain’s peacock pheasant Polyplectron germaini and Grey-faced Tit Babbler Macronous kelleyi) of the three restricted-range species that define the South Vietnamese Lowlands Endemic Bird Area (EBA) (Stattersfield et al. 1998). Therefore, the Logo - Xamat national park qualifies for inclusion within this EBA. Among the 8 species listed in the 2000 IUCN Red List of Threatened Species (IUCN 2000) or the Red Data Book of Vietnam (Anon. 1992), 4 are characteristic of forest habitats (siamese fireback, germain's peacock pheasant, Great Hornbill and Bar-bellied pitta) and 4 are characteristic of wetland habitats (Stork-billed kingfisher, sarus crane, asian openbill and Woolly-necked Stork).